2020
DOI: 10.2174/1389557520666200807133659
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Calcium Signaling in Glioblastoma Multiforme: A Therapeutic Promise for Natural Products

Abstract: : Glioblastoma multiforme (GBM) continues as one of the most lethal cerebral cancers despite standard therapeutic modalities, such as maximum surgical resection and chemoradiation. The minimal effectiveness of existing therapies necessitates the development of additional drug candidates that could improve the prognosis of GBM patients. Accumulating evidence suggests that calcium (Ca2+) is involved in the processes of cell proliferation, metastasis, angiogenesis, migration, and invasiveness. Therefore, Ca2+ co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 223 publications
0
5
0
Order By: Relevance
“…For the KEGG pathway analysis, we found that these target genes that might be regulated by hypomethylated enhancer regions were enriched in some GBM-related KEGG pathways. As the significantly enriched pathway (hsa04020, hsa04724) in this study, Afshari et al [ 35 ] showed that calcium signaling pathway is involved in the processes of cell proliferation, metastasis, angiogenesis, migration, and invasiveness. Moreover, glutamatergic and calcium signaling may promote glioblastoma formation by metabolic reprogramming and genetic switching or upregulate the levels intracellular Ca 2+ to increase glutamate release [ 36 ].…”
Section: Resultsmentioning
confidence: 57%
“…For the KEGG pathway analysis, we found that these target genes that might be regulated by hypomethylated enhancer regions were enriched in some GBM-related KEGG pathways. As the significantly enriched pathway (hsa04020, hsa04724) in this study, Afshari et al [ 35 ] showed that calcium signaling pathway is involved in the processes of cell proliferation, metastasis, angiogenesis, migration, and invasiveness. Moreover, glutamatergic and calcium signaling may promote glioblastoma formation by metabolic reprogramming and genetic switching or upregulate the levels intracellular Ca 2+ to increase glutamate release [ 36 ].…”
Section: Resultsmentioning
confidence: 57%
“…As the most prominent brain tumor for adults, GBM presents considerable invasion ability, extreme aggressive behavior, and chemoradiation resistance 24,25 . Total surgical resection accompanied by radiotherapy and concurrent chemotherapy with alkylating agent TMZ remains the primary care line, extending patients' survival by just 2 months in total 26,27 . Novel therapeutic strategies that boost clinical outcomes are therefore desperately needed 28 .…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Total surgical resection accompanied by radiotherapy and concurrent chemotherapy with alkylating agent TMZ remains the primary care line, extending patients' survival by just 2 months in total. 26,27 Novel therapeutic strategies that boost clinical outcomes are therefore desperately needed. 28 The present study assessed Zerumbone to suppress GBM cancer cell development in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, due to the unwanted side effects of chemotherapeutic agents and poor prognosis after treatment with these conventional methods, there is an urgent need to find out new potential anti-cancer compounds with low adverse effects and high effectiveness. 6,7 In recent years, herbal medicines and natural products have received more attention in the treatment of many cancers due to their low toxicity, high efficacy, and broad-spectrum properties. [8][9][10] One of these natural compounds that have shown capability in the treatment of cancer is zerumbone.…”
Section: Introductionmentioning
confidence: 99%
“…5 However, due to the unwanted side effects of chemotherapeutic agents and poor prognosis after treatment with these conventional methods, there is an urgent need to find out new potential anti-cancer compounds with low adverse effects and high effectiveness. 6,7…”
Section: Introductionmentioning
confidence: 99%